New Results for Some Generalizations of Starlike and Convex Functions - Ali Ebadian; Nafya Hameed Mohammed; Ebrahim Analouei Adegani; Teodor Bulboacă (Journal of Function Spaces)
The purpose of the current paper is to investigate several various problems for the categories STLs,SNe∗, and other related categories such as various new outcomes for the coefficients of f, together with majorization issues, the Hankel determinant, and the logarithmic coefficients with sharp inequalities and differential subordination implications.